Real-life clinical practice in Spain in the setting of new drug availability for ITP treatment. A Delphi-based Spanish expert panel consensus - Tomás José González-López; Abelardo Bárez; Ángel Bernardo-Gutiérrez; Silvia Bernat; Fernando Fernández-Fuertes; José María Guinea de Castro; Reyes Jiménez-Bárcenas; Isidro Jarque (Platelets)
Immune thrombocytopenia (ITP) is a common autoimmune hematological disorder. Despite this, diagnosis is still challenging due to clinical heterogeneity and the lack of a specific diagnostic test. New findings in the pathology and the availability of new drugs have led to the development of different guidelines worldwide. In the present study, the Delphi methodology has been used to get a consensus on the management of adult patients with ITP in Spain and to help in decision-making. The Delphi questionnaire has been designed by a scientific ad hoc committee and has been divided into 13 topics, with a total of 127 items, covering the maximum possible scenarios for the management of ITP. As a result of the study, a total consensus of 81% has been reached. It is concluded that this Delphi consensus provides practical recommendations on topics related to diagnosis and management of ITP patients to help doctors to improve outcomes. Some aspects remain unclear, without consensus among the experts. Thus, more advances are needed to optimize ITP management.